Space maintainer ‘Y model’ as a preventive orthodontic treatment for paediatric patients: a case report - Laelia Dwi Anggraini; S. Sunarno; Rinaldi Budi Utomo; Dibyo Pramono (Dental Journal (Majalah Kedokteran Gigi), 2021)
Background: Caries is one of the most common oral diseases that occur among children. Caries and dental trauma in children may cause early tooth loss, also known as premature loss, and result in occlusion abnormalities caused by the dental arch narrowing. A space maintainer is a preventive orthodontic appliance designed to maintain a narrow arch to prevent premature loss. Purpose: This study aims to describe the treatment of a case of space management in a patient with premature loss by using the space maintainer ‘Y model’. Case: An eight-year-old boy was accompanied by his mother, complaining that the lower posterior right tooth had been extracted. The mother was worried that the new tooth would have an overlapping growth. Case Management: The diagnosis was mandibular primary molar loss. The study cast was analysed based on Moyers 2.62 cm, Huckaba 2.24 mm, and curve determination 2.40 mm. The mandibular removable space maintainer treatment was performed on the patient and was followed by nine control visits every week. The outcome was a successful treatment from the use of the space maintainer ‘Y model’. Conclusion: The space maintainer treatment with the Y model in the paediatric patient showed a good result, evidenced by the tube opening of 1.2 mm, showing that the appliance followed lateral jaw growth.